L'integrazione tra servizi di monitoraggio e fruizione evoluta, per una sostenibilità economica dei nuovi sistemi di salvaguardia e valorizzazione del patrimonio culturale - Corini, Gianfranco; Monteleone, Antonio; Dore, Nicole (Archeomatica, 2018)
We present the purposes of the ArTeK Project – Satellite enabled Services for Preservation and Valorization of Cultural Heritage which aims to develop services based on space and ICT technologies for the monitoring of Cultural Heritage. A fundamental aspect of the ArTeK project consists in the joint provision of services provided to the safeguarding, management and use of the cultural heritage. These are elements that, although different from each other (by type of market, business model, etc.), should be put in place, in order to avoid the risk of carrying out only partial interventions, not correlated with other important aspects of the scenario overall and therefore ends in themselves and economically not advantageous.